PERANCANGAN SISTEM INFORMASI E-COMMERCE BERBASIS WEBSITE PADA PT. BIMANTARA SAKTI PERSADA MENGGUNAKAN METODE WATERFALL (INTI Nusa Mandiri, 2026)
The development of digital technology encourages companies to implement information systems with the aim of improving operational effectiveness and competitive ability in the market. PT. Bimantara Sakti Persada, which previously conducted sales processes traditionally, faces challenges such as limitations in marketing reach, the possibility of errors in transaction recording, and delays in preparing sales reports. This study aims to design and create a website-based e-commerce information system by utilizing the Waterfall method as a solution to the existing problems. The Waterfall method is implemented through a series of steps that include needs analysis, system design, implementation, testing, and evaluation and maintenance. The designed system provides various functions such as member registration, product management, shopping cart, payment processing, and transaction verification. The system assessment is carried out by conducting functional testing using the Black Box Testing approach as well as testing the utilization of the system by the admin and sales team. The test results show that all system functions operate according to the specified requirements. Based on usage evaluation results, the system is capable of replacing the manual sales process with a more structured computerized system, thereby facilitating transaction recording and the preparation of sales reports. Comparisons of conditions before and after the system's implementation indicate an increase in efficiency in transaction management as well as ease of access to sales information in real time. Thus, the developed web-based e-commerce information system can support PT. Bimantara Sakti Persada's sales process more effectively and in an integrated manner